People's Bank of Nigeria : history and growth (Kano Nigeria : Triumph, 1990)
Chapters in this book reflect divergent views and backgrounds of the contributors, from policy makers, implementors, professionals, members of the public to journalists on the People's Bank of Nigeria. This is a useful guide to the history and growth of the people's Bank of Nigeria.
osc 16/05/2018
Loans
Keywords: Banking